Organosilicon(IV) Complexes of 3-Hydroxy-2-pyridine Carboxylic Acid and 2-Pyridine Carboxylic Acid and Their Antimicrobial Activity - MALHOTRA, R. (Asian Journal of Chemistry, 2009)
Organosilicon(IV) complexes of the types R2Si(Cl)n(L1-L2)2-n where (R = methyl, ethyl or phenyl, L1 = 3-hydroxy-2-pyridinecarboxylate and L2 = 2-pyridine carboxylate, n = 0 or 1) have been synthesized and characterized by elemental analyses, IR, 1H, 13C and 29Si NMR spectroscopy. These studies indicated that ligands L1 and L2 chelated through nitrogen of pyridine and oxygen of carboxylate group and have penta- and hexa-coordinated state around the silicon atom. The ligands and their organosilicon complexes have been screened for their in vitro antimicrobial activities against several fungi and bacteria in order to explore their possibility to use as biocidal agents.